Board Characteristics and Capital Structure of Malaysia Consumer Products Sector - Kuah Yoke Chin; Zuriawati Zakaria (The International Journal of Banking and Finance, 2018)
This study investigated the relationship between board characteristics and capital structure, namely total debt, short-term debt, and long-term debt of firms in the Malaysian consumer products sector for the period 2010 to 2014. Based on 109 firms selected for the study, the firms’ decision about capital structure regardless of total debt, short-term debt or long-term debt is not influenced by the size of the board. However, if the board membership constitutes more independent directors, the proportion of short-term debt is even higher than the long term-debt. Board meetings were found to have a significantly negative influence on firms’ decisions concerning total debt financing. The findings also revealed that large firms hold more short-term and long-term debts when there is an increase in the number of members on the board. The firms that have been long in existence focused more on short-term debt financing and their growth in terms of capital expenditure. Consequently, the total debt of the firms also increased.